Impact of manganese on the hippocampus metabolism in the context of MEMRI: a proton HRMAS MRS study. Issue 2 (8th January 2015) - Daoust, A.; Barbier, E. L.; Bohic, S.; Stupar, V.; Maunoir-Regimbal, S.; Fauvelle, F.
Graphical Abstract: Abstract: Manganese enhanced MRI (MEMRI) offers many possibilities such as tract tracing of neuronal pathways and functional imaging in vivo . This technique necessitates a direct or indirect acute injection of MnCl2 in the brain. Unfortunately, local concentrations of Mn 2+ and its impact on metabolism after a single injection remain largely unknown. In this study, we combined in vivo MEMRI and ex vivo Proton High Resolution Magic Angle Spinning MRS ( 1 H HRMAS MRS) to investigate the delayed impact of Mn 2+ on rat hippocampal metabolism. MEMRI images were acquired 24 h after MnCl2 injection in the dentate gyrus of the rat hippocampus at two different Mn 2+ doses: low (8 nmol; n = 16) and high (500 nmol; n = 10). The low Mn 2+ dose had almost no impact on hippocampal metabolism while the high dose altered the amplitude of several metabolites (up to +54% for Glu and −71% for Asp). Moreover, at this high dose, the paramagnetic properties of Mn 2+ led to a broadening of the resonances of several organic acids (lactate, glutamate, N -acetyl aspartate etc. ), suggesting a chelation of Mn 2+ and an impact on Mn 2+ relaxivity. Metabolite amplitudes were well correlated with the Mn 2+ concentrations measured with an MRI T 1 -map (glutamate: R 2 = 0.8, p = 0.02; phosphoethanolamine: R 2 = 0.9, p = 0.0004; γ-aminobutyrate: R 2 = 0.7, p = 0.005 and phosphocholine: R 2 = 0.6, p = 0.04). To conclude, HRMAS is well suited to investigate Mn 2+ impact on the metabolism. The low Mn 2+ dose (8 nmol) usually used in the MEMRI experiment does not impact the hippocampal metabolism. The chelation of Mn 2+ and its impact on relaxivity suggests an over-estimation of the Mn 2+ concentration when measured through a T 1 map.